Linking the religious and social environment to sexual minority mental health. - Todd, Nathan R.; Nguyễn, Daniel M.; Blackburn, Allyson M.; La, Raymond; Kim, Seungju (American Journal of Community Psychology, 2025)
In the United States, mental health disparities persist between sexual minorities – people who identify as lesbian, gay, bisexual, or other nonheterosexual identifications – and heterosexuals. Although research shows that structural stigma in one's environment may contribute to such disparities, little research has examined religious environment as a source of structural stigma for sexual minorities. Given historic and ongoing religious‐based sexual minority stigma, such research is needed. Thus, we conducted a secondary analysis of the Household Pulse Survey (n = 824,900) to test whether facets of the religious environment (i.e., presence of places of worship and conservative Christian adherents in one's U.S. state of residence) are associated with anxiety and depression. We test if associations are stronger for sexual minorities compared to heterosexuals and if associations remain significant after including other facets of the social environment (same‐sex households, political conservatism, and urbanicity) and individual‐level controls. We found that when considered separately, religious and social environmental factors demonstrated stronger associations with anxiety and depression for sexual minorities relative to heterosexuals, even after controlling for individual variables. Findings were more nuanced for integrated models. Overall, we address a gap in the literature by examining religion as a structural part of one's environment. Highlights: Disparities in mental health persist between sexual minorities and heterosexualsWe show the religious environment is associated with mental health for sexual minoritiesThe religious environment should be considered when working with sexual minority communities